Age-depth model of Baltic Sea sediment core EMB201/13-4 - Daniela J M Müller; Ina Neugebauer; Rebecca J Kearney; Markus J Schwab; Oona Appelt; Markus Czymzik; Jérôme Kaiser; Helge Wolfgang Arz; Achim Brauer (PANGAEA, 2025)
In the Baltic Sea sediments, radiocarbon dating is influenced by varying influx of old carbon and reservoir age changes, which challenges the construction of robust age models. In homogeneous sediments formed during cold periods, radiocarbon ages are too old due to resuspension of old carbon by bottom currents (Moros et al. 2020). In contrast, within laminated sediments formed during warmer climates the influence of old carbon is negligible and ages from these sediments have been used for age modelling using the global-average marine reservoir age (Moros et al. 2020), since a well-defined regional marine reservoir is lacking. This dataset provides results from Bayesian age depth modelling in OxCal (v4.4) for core EMB201/13-4 retrieved from the Western Gotland Basin in the Baltic Sea. The age model is based on published radiocarbon ages from two Western Gotland Basin sediment cores (Moros et al. 2020; Häusler et al. 2017) that were transferred onto our sediment core, (ii) tephra-derived ages from the four tephra isochrons in our core, and (iii) a regional marine reservoir age calculated from the age offset between our tephra and radiocarbon ages from the same laminated sediment intervals in core EMB201/13-4. First, our regional marine reservoir age of 250±50 years was subtracted from all radiocarbon ages and then the age model was calculated in OxCal (v4.4) using a P_Sequence (1,0.2,U(- 2,2)) and IntCal20 (Bronk Ramsey, 2008; Bronk Ramsey, 2009; Bronk Ramsey and Lee, 2013; Reimer et al., 2020). The age model spans 561.8-57 cm depth (c. 6935-347 cal. a BP).
In: Müller, DJM et al. (2025): Major element geochemistry of tephra glass shards and age model construction in Baltic Sea sediment cores EMB201/13-4 and POS507/29-2 [dataset bundled publication]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.984844 (DOI registration in progress)